Leaching of Iron and Zinc into Food Simultant from Tin Can Packaging - Lilis Sulistiawaty; Imas Solihat; Arie Pratama Putra (Syarif Hidayatullah State Islamic University, 2019)
Cans are widely used as primary packaging in various food products. Ferrous (Fe) and zinc (Zn) metal as the constituent components in the manufacture of can packaging bodies can experience corrosion and dissolve in food so that it will affect food quality and finally affect to health. This study aimed to determine the content of Fe and Zn metal at different treatments (time) with 3% acetic acid and vegetable oil as food simulators on can packaging using Atomic Absorption Spectrophotometer (AAS). The results of the analysis showed that the range of Fe and Zn metal content in 3% acetic acid food simulants were respectively 0.15-27.46 mg/kg and 0.00060.007 mg/kg, while in vegetable oil simulants 3% Fe and metal content Zn were 0.6-2.46 mg/kg and 0.00040.0025 mg/kg with 80-100% recovery, respectively. Thus, food from can packaging should not be exposed to oxygen for a long time, especially when it has been opened because it will increase the leaching of Fe and Zn metals from the packaging into food.